The Promise of Commons in the context of PES Markets : Learning of FES in India - Choudhury, Pranab R. (2023)
Pranab R Choudhury CGIAR SEMINAR SERIES Payments for Ecosystem Services: Win-Win Solutions? Co-organized by IFPRI, the CGIAR, and Germany’s Federal Ministry for Economic Cooperation and Development (BMZ) Session at Tropentag 2023 SEP 21, 2023 - 7:45 TO 9:15AM EDT